2020
DOI: 10.1212/wnl.0000000000008872
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of N -acetylcysteine therapy for RYR1 -related myopathies

Abstract: ObjectiveTo investigate the efficacy of N-acetylcysteine (NAC) for decreasing elevated oxidative stress and increasing physical endurance in individuals with ryanodine receptor 1-related myopathies (RYR1-RM).MethodsIn this 6-month natural history assessment (n = 37) followed by a randomized, double-blinded, placebo-controlled trial, 33 eligible participants were block-randomized (1:1) to receive NAC (n = 16) or placebo (n = 17), orally for 6 months (adult dose 2,700 mg/d; pediatric dose 30 mg/kg/d). The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…NAC did not decrease the oxidative stress in these patients but showed clinically improved physical endurance. The dose in individuals with RYR1-RM was 2,700 mg/d for adults and the pediatric dose was 30 mg/kg/d [49]. Dy 2J /dy 2J mice received 150 mg/kg/d but it should be pointed out that the optimal dose of NAC is unclear, and studies may show equal efficacy at lower doses or greater efficacy at higher doses [50].…”
Section: Discussionmentioning
confidence: 99%
“…NAC did not decrease the oxidative stress in these patients but showed clinically improved physical endurance. The dose in individuals with RYR1-RM was 2,700 mg/d for adults and the pediatric dose was 30 mg/kg/d [49]. Dy 2J /dy 2J mice received 150 mg/kg/d but it should be pointed out that the optimal dose of NAC is unclear, and studies may show equal efficacy at lower doses or greater efficacy at higher doses [50].…”
Section: Discussionmentioning
confidence: 99%
“…NAC has also been evaluated in individuals with ryanodine receptor 1-related myopathies. However, this antioxidant agent, administered orally for six months, did not reduce OS in these patients [66].…”
Section: Would Nac Be Useful As a Therapy For Dysferlinopathies?mentioning
confidence: 75%
“…Based on these data, NAC was recently tested via clinical trial in RYR1-RM patients, where a non-significant trend toward improvement was observed (Todd et al, 2020). These observations open the prospective of polytherapy as a potential treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, as of yet none of these targets has successfully translated to patients, though Nacetylcysteine was tested in a recently completed clinical trial (ClinicalTrials.gov identifier: NCT02362425), where it failed to achieve its primary endpoint (Todd et al, 2020). There is thus a critical need to identify and develop new treatment strategies.…”
Section: Introductionmentioning
confidence: 99%